(3GdhQO Gdefghd GdCUaj aj ehdO GdQShd GdoeUWais - (3eMji GdOjf oeUWai Hf ceGd GdOjf Ydj GdHcQjs; (3eUWaj GdHcQj , eUWaj Hf ceGd GdOjf Hf Ydj GdHcQj GdUOjbj GdNdhJj,J (B1162 (3g` s
(3ChdgG (B:s
(3hHYO bO WdH efi HYV GdCMHGH GdCNjGQ GNJUGQ GdehdO GdPi SejfGg GdehQO GdQhi ai GdehdO GdfHhi aHGOQJ HMhd GdLHGQ ddGbJUGQ Ydi eGdG HO efg ef GdCNHGQ s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG hehdGfG eMeO GdCejf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B271 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B449s
Keywords: (3GdJGQjNs